Effectiveness of Education Program on Correct Posture and Daily Exercise in Reducing and Preventing Back Pain in Patients with Chronic Low Back Pain, Kuean Sub-district, Kosumpisai District, Mahasarakam Province - Hanchanlert, Yotsak (Journal of Health Science of Thailand, 2017)
Chronic low back pain is one of the top five major health problems in Kuean Sub-district, Kosumpisai District, Mahasarakam Province. This study aimed to assess the effects of an education program on correct posture in daily life together with therapeutic exercise to reduce and prevent low back pain as well as to study the effectiveness of physical therapy service in a primary care unit. Participants in this study were 36 patients with chronic low back pain in Kean subdistrict, Kosumpisai District, Mahasarakam province. Inclusion criteria comprised an average age of less than 60 years old and had low back pain in the past three months without signs of weakness or history of spinal surgery. The program activities included education on correct postures in everyday life and 3 sessions of group therapeutic exercises guided by a physical therapist. Assessment of pain and disability was conducted by using visual analogue scale pain and Roland - Morris disability questionnaire before and after intervention. The results showed that there were significant reduction of pain score (83.33%) and increase of functional work capacity (77.27%). Moreover, within 2 years of the intervention only 13.88% of total participants had come to Kosumpisai Hospital for treatment. Therefore, we concluded that the program of education on correct posture and therapeutic exercise could prevent and reduce back pain, and improve functional work capacity. In addition, proactive physical therapy service in primary care unit could improve knowledge and reduce recurrence of low back pain in patients.